ANALISIS UNJUK KERJA SISTEM PENERIMA RADIO NEC PASOLINK DI HOTEL GRAND MAHKOTA PONTIANAK - ., M. Asep Prayana (Fakultas Teknik, 2016)
Analysis of the performance of NEC's PASOLINK system radio receivers at the grand crown pontianak used to compare the results of the power received on a radio device with power received in the calculation results. To compare the results of the received power at a radio device with the calculation results of received power required calculation parameters are: Feeder Loss, Loss Rain, Free Space Loss, Gain Antenna, EIRP, and Accept Input Power Receiver. Based benchmarks used for acceptance refers to the standards of the International Telecommunication Union (ITU), namely Pr -50 dBm then proceeds received power on the device is very good radio. From the calculation of the received power obtained without the K factor is -53.454 dBm. Whereas the results of power received by the K factor is -54.784 dBm. Based benchmarks used for acceptance refers to the standards of the International Telecommunication Union (ITU), namely Pr = < -50 s / d -88 dBm then the power received on the calculation HSIL good enough. Walaupaun data retrieval is done with the conditions and at different times, the results gained acceptance fairly stable. Measurement used to power the results received signal referring to the standards of the International Telecommunication Union (ITU), namely Pr> - 50 dBm, then it is very good, Pr = < -50 s / d - 88 dBm, then it is good enough, Pr < - 88 dBm, bad. Preventive maintenance on radio equipment NEC PASOLINK should run well because it aims to prevent equipment damage during surgery. Preventive maintenance is done on a scheduled basis according to the estimated life of the equipment. Results received power at a radio device in the grand crown of october until november is very good because the received power is greater than -50 dBm. The best results obtained on 21 October 2015 in the amount of -35.7 dBm. Keywords: Microwave, Network Access, Link Budget, Radio NEC PASOLINK